Frequency of Undiagnosed Diabetes Mellitus in Patients Presenting with Acute Stroke in a Medical Emergency - Aleena Farooq, Mariam Tariq, Saad Sultan, Anam Balal Khan, Memoona Omer, Qurat-Ul-Ain (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of this study was to assess the prevalence of undiagnosed DM in individuals who came with an acute stroke in a medical emergency. Methods: This descriptive cross-section study was carried out at the Shifa International Hospital’s Department of Medicine in Islamabad, Pakistan from 24-11-2020 to 23-05-2021. A total number of 150 patients of either gender presenting with acute stroke were included. Venous blood samples from all patients were sent to hospital laboratory for determination of HbA1c levels. Diabetes (DM) was labeled if HbA1c > 6.0%. Results: The mean age was 54.04±10.25 years. The mean duration of stroke was 14.92±7.99 days. There were 92 (60.67%) males and 58 (39.33%) female patients. 61 (40.67%) out of 150 patients were smokers. Undiagnosed diabetes mellitus was found in 42 (28.00%) patients. Conclusion: The frequency of newly diagnosed diabetes is high among patients with ischemic stroke. So, it is recommended that every patient who present with ischemic stroke, should be sorted out for diabetes mellitus. However, it is also required that every setup should have their surveillance in order to know the frequency of the problem. Keywords: undiagnosed diabetes mellitus, acute stroke, diabetes mellitus (DM),